INNOVATIVE TECHNOLOGIES IN ENGLISH LANGUAGE LEARNING PLACE - Sarvinoz Mamasoliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
Language is the primary means of communication, it is difficult for you to imagine the existence and development of human society. At a time of great changes in our world today, the demand for learning foreign languages is growing in our country, the study of English is very deeply rooted. At the initiative of the President, English is widely taught in all fields of education. The use of technology in the process of learning English is yielding effective results.